Pragmatic analysis of the technical jargon of UNALM students - Loayza Maturrano, Edward Faustino (2013)
This paper focuses on the study of technical slang lexicon for students from the Universidad Nacional Agraria La Molina by pragmatic qualitative analysis of the multiple variations in expression and meaning, and its contextualization within the variety communicative situations that are expressed. To do this, hermeneutical method is used, recognizing, interpreting and characterizing the plurality of messages and meanings of social and pragmatic type. The results transmit the nature of the reality of the sociolinguistics and pragmatic situations of the speech.